Analisis Pengembalian Keputusan Investasi Saham Dengan Pendekatan Capital Asset Pricing Model (CAPM) pada Perusahaan Perbankan Terdaftar di Bursa Efek Indonesia - Nurmala, Nurmala (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT The investors chose the banking shares because the management of this banking is overseen and regulated by Financial Services Authority in a transparent manner. This banking world will always be professional and transparent in managing public funds. It certainly will provide trust and positive value in the eyes of the community. The problem of this research is how to make Stock Investment Decision in accordance with Capital Asset Pricing Model (CAPM) Method on Banking Companies registered in Indonesia Stock Exchange. The purpose of this research is to analyze the decision of stock investment in accordance with Capital Asset Pricing Model (CAPM) method in Bankingcompanies registered in Indonesia Stock Exchange.The method used in this research is descriptive quantitative method and data are collected by documentation technique. The data analysis technique is used to calculate Individual Shares Return Rate (Ri), Risk Free Return (Rf), Market Rate (Rm), Premium Risk (Rp), expected Return Rate E (Ri), and to help the efficiency and the decision of Stock Investments.Based on the results of the research, it can be seen that the risk with the lowest expected stock return is 0.340 and the highest expected rate of return is equal to 0.00532. There are 25 companies stocks included in the category of efficient stocks and 13 companies stocks included in the category of inefficient stocks among 38 companies stocks taken as this research sample. These stocks have greater Ri value than E (Ri) or [Ri> E (Ri)]. The investment decision taken by the investor is to buy the stocks.